Long-term prognostic value of left atrial longitudinal strain in a low-risk community-based cohort. (3rd October 2022) - Zhubi Bakija, F; Bagyura, Z; Fabian, A; Ferencz, A; Lakatos, B; Ujvari, A; Kiss, L; Csobay-Novak, C; Jermendy, A; Szelid, Z; Soos, P; Kovacs, A; et al.
Abstract: : Numerous studies established the significant predictive value of left ventricular (LV) global longitudinal strain (GLS) on adverse clinical outcomes in various cardiac diseases. Despite the well-known importance of left atrial (LA) mechanics in diastolic function, data are scarce regarding the prognostic power of LA longitudinal strain and its potential added value in the risk stratification of a low-risk population. Accordingly, our aim was to determine the long-term prognostic importance of 2D speckle-tracking echocardiography-derived peak atrial longitudinal strain (PALS) in a community-based screening sample comprising of low-risk adult individuals. Three hundred fourteen volunteers were retrospectively identified from a population-based screening program (mean age 62±11, 58% female) with a median follow-up of 9.5 years. All subjects who participated in the screening program underwent 2D echocardiography to measure LV volumes and ejection fraction (EF), LV GLS and PALS, as well as low-dose cardiac CT to determine the Agatston score. The primary endpoint was all-cause mortality. Thirty-nine subjects (12.4%) met the primary endpoint. Subjects with adverse outcome had significantly decreased LV GLS (dead vs. alive; −19.2±4.3 vs. −20.6±3.5%, p<0.05) and PALS (32.3±12.0 vs. 41.8±14.2%, p<0.001), whereas LV EF did not show a difference between the two groups (51.1±7.0 vs. 52.1±6.2, %, p=NS). By multivariable Cox regression analysis, PALS (hazard ratio 0.970 [95% CI: 0.943–0.998], p<0.05) and Agatston score were independently associated with all-cause mortality, whereas GLS was not (hazard ratio 1.008 [95% CI, 0.919–1.105], p=NS). Furthermore, we dichotomised the population based on PALS values using a guideline-directed cut-off of 39%. In subjects with lower PALS values, the risk of all-cause mortality was almost 2.5 times higher than in subjects with PALS values above 39% (hazard ratio 2.499 [95% 1.334–4.682], p<0.05) as shown on the Kaplan-Meier curve (Figure 1). Beyond the assessment of LV EF and LV GLS, PALS offers incremental value in cardiovascular risk stratification in a community-based cohort. PALS was found to be the only significant and independent predictor of long-term mortality among other echocardiographic functional parameters. Our results emphasize the importance of a thorough evaluation of LA mechanics even in a low-risk population. Funding Acknowledgement: Type of funding sources: None.